Liver tissue metabolically transformed by alcohol induces immune recognition of liver self-proteins but not in vivo inflammation - Duryee, Michael J. (Am J Physiol Gastrointest Liver Physiol, 2018)
Precision-cut liver slices (PCLSs) provide a novel model for studies of alcoholic liver disease (ALD). This is relevant, as in vivo ethanol exposure does not appear to generate significant liver damage in ethanol-fed mice, except in the National Institute on Alcohol Abuse and Alcoholism binge model of ALD. Previous studies have shown that the two metabolites of ethanol consumption, malondialdhyde (MDA) and acetaldehyde (AA), combine to form MDA-AA (MAA) adducts, which have been correlated with the development and progression of ALD. In this study, murine PCLSs were incubated with ethanol and examined for the production of MAA adducts. PCLSs were homogenized, and homogenates were injected into C57BL/6 mice. PCLSs from control-, pair-, and ethanol-fed animals served as targets in in situ cytotoxic assays using primed T cells from mice hyperimmunized with control or ethanol-exposed PCLS homogenates. A CD45.1/CD45.2 passive-transfer model was used to determine whether T cells from the spleens of mice hyperimmunized with PCLS ethanol-exposed homogenates trafficked to the liver. PCLSs incubated with ethanol generated MAA-modified proteins in situ. Cytotoxic (CD8(+)) T cells from immunized mice killed naïve PCLSs from control- and pair-fed mice in vitro, a response that was blunted in PCLSs from ethanol-fed mice. Furthermore, CD45.1 CD8(+) T cells from hyperimmunized mice trafficked to the liver but did not initiate liver damage. This study demonstrates that exposure to liver tissue damaged by ethanol mediates robust immune responses to well-characterized alcohol metabolites and native liver proteins in vitro. Moreover, although these proinflammatory T cells traffic to the liver, these responses appear to be dampened in vivo by locally acting pathways. NEW & NOTEWORTHY This study shows that the metabolites of ethanol and lipid breakdown produce malondialdehyde-acetaldehyde adducts in the precision-cut liver slice model system. Additionally, precision-cut liver slices exposed to ethanol and harboring malondialdehyde-acetaldehyde adducts generate liver-specific antibody and T cell responses in the spleens of naïve mice that could traffic to the liver.